Pneumocystis carinii pneumonia in chronic lymphocytic leukaemia. Issue 942 (13th April 2004) - Vavricka, S R; Halter, J; Hechelhammer, L; Himmelmann, A
Abstract : Pneumocystis carinii pneumonia in patients with chronic lymphocytic leukaemia (CLL) who have not been treated with fludarabin are rare, although clinically relevant CD4 T-cell depletion can occur in longstanding CLL without prior treatment with purine analogues. A 52 year old woman is reported who was on long term treatment with chlorambucil and taking a short course of prednisone for familial CLL before she developped progressive dyspnoea, and P carinii pneumonia was diagnosed in bronchoalveolar lavage fluid. Despite treatment with high dose co-trimoxazole the patient died.